Desain Modul Rawat Inap untuk Sistem Informasi Manajemen Rumah Sakit (Studi Kasus: Rumah Sakit Universitas Mataram) - I Gede Restu Astikadeni; Ida Bagus Ketut Widiartha; Dwi Ratnasari (Journal of Computer Science and Informatics Engineering (J-Cosine), 2026)
Advances in information technology have encouraged healthcare services to adopt Hospital Management Information Systems (HMIS) to improve operational efficiency. However, the inpatient module at Mataram University Hospital still has issues such as irrelevant form content, a complex interface, and inefficient navigation. This study aims to design a prototype of the inpatient module using the User-Centered Design (UCD) method. UCD places users at the center of the design process and ensures that the system addresses actual needs. The development process followed the UCD stages, including understanding the context of use, specifying user requirements, producing design solutions, and evaluating the design iteratively through wireframes and prototypes. Evaluation was conducted using the User Experience Questionnaire (UEQ), and the system achieved high scores in five out of six aspects: Attractiveness, Clarity, Efficiency, Stimulation, and Novelty. These results indicate that the prototype offers a positive user experience and is suitable for future implementation and development.